The Significance of CD4 to the Number of Grown Candida Colonies in Oral Candidiasis Patients with HIV / AIDS - Dwi Murtiastutik1 , Cita Rosita Sigit Prakoeswa1 , Indah Setyawati Tantular2,3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Basic data of this study showing isolates mostlytaken from male than female (77.5% and 22.5%). Themost age group is productive age groups in the agerange of 26-35 years with 20 subjects (50%). In 2017report of the Directorate General of Disease Controland Environmental Health, Ministry of Health Republicof Indonesia, found HIV/AIDS patients more malethan women, and related more common in young adultwhich makes it more likely to engage in unsafe sexualbehavior that is at risk of HIV transmission (8). Thedomicile of HIV / AIDS patients with OC mostly camefrom Surabaya (90%). This is because most patientshave to seek help from the nearest health center withmost patients from within the city. The isolates mostwere taken from HIV / AIDS patients with OC who hadan absolute CD4 count <100 cells / L for 28 patients(70%). This data is supported by a 2015 Indian study byKumar that showed 71.4% of patients with a CD4 cellcount <200 cells / µL obtained by the fungus growth ofCandida species from OC lesions (9).